In Situ Preparation of CsPbBr3@CsPb2Br5 Composite Assisted with Water as a Highly Efficient and Stable Catalyst for Photothermal CO2 Hydrogenation. Issue 50 (18th July 2022) - Gao, Peng; Cui, Zihao; Liu, Xiaolei; Wu, Yaqiang; Zhang, Qianqian; Wang, Zeyan; Zheng, Zhaoke; Cheng, Hefeng; Liu, Yuanyuan; Li, Qing; Huang, Baibiao; Wang, Peng
Abstract: Lead halide perovskite has triggered a lot of research due to its superior optical properties. However, halide perovskite materials have poor environmental stabilities and are easily affected by external factors such as water and heat, resulting in structural decomposition and performance failure. Contrary to this commonplace concept, it is found that CsPbBr3 (CPB) can convert to CsPb2 Br5 (CP2B5) partially when meeting a small amount of water, and the CsPbBr3 @CsPb2 Br5 (CPB@CP2B5) composite is synthesized by an in situ method accordingly. The CPB@CP2B5 composite shows an enhanced catalytic performance compared with pure CPB, as well as a dramatically synergistic effect of photo and thermal for catalytic CO2 hydrogenation. The CO production rate of CPB@CP2B5 is determined as 69 μmol g −1  h −1 under light irradiation at 200 °C, which is 156.8 and 43.4 times higher than that under pure photo (0.44 μmol g −1  h −1 ) and pure thermal (1.59 μmol g −1  h −1 ) condition, respectively. Meanwhile, the CPB@CP2B5 sample is also stable, which shows no significant decline in the catalytic activity during 8 cycles of repeated experiments. The probable mechanism is explored by utilizing a series of in situ characterizations. Abstract : Lead halide perovskite has triggered a lot of research due to its superior optical properties. However, halide perovskite materials have poor environmental stabilities and are easily affected by external factors such as water and heat, resulting in structural decomposition and performance failure. Contrary to this commonplace concept, CsPbBr3 can convert to CsPb2 Br5 partially when meeting a small amount of water, and the CsPbBr3 @CsPb2 Br5 composite is synthesized by an in situ method accordingly. The CsPbBr3 @CsPb2 Br5 composite shows an enhanced catalytic performance compared with pure CsPbBr3, as well as a dramatically synergistic effect of photo and thermal for catalytic CO2 hydrogenation.